Night falls on Predicament Avenue [large type] - Wright, Jaime Jo (THORNDIKE PRESS LARGE PRINT Christian Fiction, 2024)
"As the walls of the house at Predicament Avenue reveal their hidden truths, two women--generations apart--discover that fear and foreboding are no respecters of time. In 1910, Effie James is committed to doing anything to save her younger sister, who witnessed a shocking murder, leaving her mute and in danger of the killer's retribution. Effie must prove what her sister saw, but when a British gentleman arrives, he disrupts Effie's quest with his attempts to locate his wife, Isabelle Addington, who was last seen at the supposed crime scene in the abandoned house at 322 Predicament Avenue. Just as Effie discovers what she seeks, she finds that the blood staining the walls will forever link her to a scandal she couldn't imagine, and to a woman whose secrets promise to curse any who would expose them.A century later, Norah Richman grapples with social anxiety and grief as she runs her late great-aunt's bed-and-breakfast on Predicament Avenue. But Norah has little affection for the house and is committed only to carrying out her murdered sister's dreams until crime historian and podcaster Sebastian Blaine arrives to investigate the ghostly legacy of the house's claim to fame--the murder of Isabelle Addington. When a guest is found dead, the incident is linked to Isabelle's murder, and Norah and Sebastian must work together to uncover the century-old curse that has wrapped 322 Predicament Avenue in its clutches and threatens far more than death"--